Agonistic behaviour and control of access to hiding places in two intertidal blennies, Lipophrys pholis and Coryphoblennius galerita (Pisces: Blenniidae) - Faria, Cláudia Barreiros Macedo de (2012)
In this study we investigated the relationships between dominance rank and access to shelters in captive groups of Lipophrys pholis and Coryphoblennius galerita, as well as the effects of group size and shelter availability. Dominance rank was strongly correlated with size in juvenile L. pholis and with sex and size in adult C. galerita, males being dominant over females of similar size. Access to shelters was significantly correlated with dominance rank. For both species, most interactions occurred out of shelters. Direct disputes over shelters were always initiated by the dominant fish and the initiator was always the winner. The rate of aggression per fish per unit time decreased with an increase in the number of fish in L. pholis but not in C. galerita. No significant differences were found in groups differing in the number of shelters. C. galerita showed a higher rate of agonistic interactions and a higher proportion of overt aggression than L. pholis. It is suggested that one of the functions of agonistic interactions in these fishes is the control of a set of shelters, in the network of pathways used by each individual within its home range, minimising the time required to hide in case of danger.